Ikterus Obstruktif Pada Penderita Tumor Pankreas - Farras Ajeng Octaviany Fazeny (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Pancreatic carcinoma is a rare malignancy due to its relatively low incidence but it is ranked 8th in the world for its mortality. Obstructive jaundice is the results of malignancy that in most cases occurnot only due to pancreatic carcinoma but also cholangiocarcinoma. The purpose of this study to find out the description regarding obstructive jaundice in patients with pancreatic tumors at RSUD Dr. H. Abdul Moeloek in 2017-2019. This study was an This current research used descriptive approach and medical record to obtain primary data with40 peoplebecame the research sample. The result showed In general, the age distribution frequency of patients with pancreatic tumors and diagnosed with obstructive jaundice was >50 years old of 30 people (75.0%), 23 of them weremales (57.5%). Mostly, their direct bilirubin levels was abnormal of 37 people (92.5%), same as their total bilirubin levels that regularly abnormal of 39 people (97.5%), supporting investigation on patients by using USG of 28 people (70.0%). The frequency distribution of patient operations was 28 people (70.0%). The conclusion is serious treatment is necessary for pancreatic tumor patients with obstructive jaundice for supporting their recovery.